Angiographic predictors of aberrant circumflex artery during cardiac catheterization. Issue 3 (12th July 2022) - Triantafyllis, Andreas S.; van Nunen, Lokien X.; Lesizza, Pierluizi; Pagourelias, Efstathios D.; Kalogeris, Aimilianos; Bouwmeester, Sjoerd; Tsinivizov, Pavlos; Kontogiannis, Nestoras; Giannakopoulos, Andreas; Poulimenos, Leonidas E.; Bennett, Johan; Teeuwen, Koen; et al.
Abstract: Objectives: To identify angiographic predictors of aberrant left circumflex artery (LCx) by comparing left main (LM) length and bifurcation angle between patients with aberrant LCx and normal anatomy. Background: Failure to recognize aberrant LCx during a cardiac catheterization may hamper correct diagnosis, delay intervention in acute coronary syndromes, and result in increased contrast volume, radiation exposure, and infarct size. Methods: We retrospectively analyzed angiograms of aberrant LCx patients and normal anatomy matched controls, in three‐participating centers. LM‐length, bifurcation angle between the left anterior descending (LAD) and the first non‐LAD branch of the LM, and procedural data were compared. Results: Between 2003 and 2020, 136 patients with aberrant LCx and 135 controls were identified. More catheters (2.4 ± 0.6 vs. 2.2 ± 0.9, p  = 0.009), larger contrast volumes (169 ± 94 ml vs. 129 ± 68 ml, p  < 0.0005), and prolonged fluoroscopy time (652.9 ± 623.7 s vs. 393.1 ± 332.1 s, p  < 0.0005), were required in the aberrant LCx‐group compared with controls. Patients with aberrant LCx had a longer LM‐length and a more acute bifurcation angle, both in caudal and cranial views, compared with controls (24.7 ± 8.1 vs. 10.8 ± 4.5 mm, p  < 0.0005 and 26.7 ± 7.4 vs. 12 ± 5.5 mm, p  < 0.0005, respectively, and 45.2° ± 12° vs. 88.8° ± 23°, p  < 0.0005 and 51.9° ± 21° vs. 68.2° ± 28.3°, p  < 0.0005, respectively). In ROC analysis, LM‐length showed the best diagnostic accuracy for detecting aberrant LCx. In multiple logistic regression analysis, a cranially measured LM‐length > 17.7 mm was associated with a 5.3 times greater probability of predicting aberrant LCx [95% CI (3.4–8.1), p  < 0.0001]. Conclusions: Our study suggests that a long LM‐length and an acute bifurcation angle can indicate the presence of aberrant LCx. We present a practical algorithm for its rapid identification.